2007
DOI: 10.1890/06-1187.1
|View full text |Cite
|
Sign up to set email alerts
|

Soil Responses to Management, Increased Precipitation, and Added Nitrogen in Ponderosa Pine Forests

Abstract: Forest management, climatic change, and atmospheric N deposition can affect soil biogeochemistry, but their combined effects are not well understood. We examined the effects of water and N amendments and forest thinning and burning on soil N pools and fluxes in ponderosa pine forests near Flagstaff, Arizona (USA). Using a 15N-depleted fertilizer, we also documented the distribution of added N into soil N pools. Because thinning and burning can increase soil water content and N availability, we hypothesized tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 63 publications
1
20
0
Order By: Relevance
“…Means with the same letter within each year are not significantly different (Fisher's LSD,α=0.05) presented) indicated N UP and root biomass increased concurrently. Lower N UP in I relative to F and IF shows site nutrient supply capacity (i.e., N MIN ) was not enhanced by irrigation and suggests native N supply capacity, not moisture availability (Groffman et al 2009;Hungate et al 2007), limited N UP at this site.…”
Section: Nitrogen Concentration and Nitrogen Contentmentioning
confidence: 88%
“…Means with the same letter within each year are not significantly different (Fisher's LSD,α=0.05) presented) indicated N UP and root biomass increased concurrently. Lower N UP in I relative to F and IF shows site nutrient supply capacity (i.e., N MIN ) was not enhanced by irrigation and suggests native N supply capacity, not moisture availability (Groffman et al 2009;Hungate et al 2007), limited N UP at this site.…”
Section: Nitrogen Concentration and Nitrogen Contentmentioning
confidence: 88%
“…Changing precipitation regimes (Zhang et al., ) and atmospheric N deposition (Erisman et al., ; Gruber & Galloway, ) can both affect plant growth and C uptake via altering soil water and N availability especially in ecosystems where they are limited (LeBauer & Treseder, ; Niu et al., ), with consequent impacts on autotrophic and heterotrophic soil respiration. Numerous previous studies have reported soil respiration responses to precipitation change (Flanagan et al., ; Liu et al., ; Suseela et al., ; Wan, Norby, Ledford, & Weltzin, ; Yan et al., ) or N addition (Chen, Li, Lan, Hu, & Bai, ; Graham et al., ; Janssens et al., ; Ramirez, Craine, & Fierer, ), but few have investigated the combined effects of these two factors (Eisenhauer, Cesarz, Koller, Worm, & Reich, ; Hungate, Hart, Selmants, Boyle, & Gehring, ; Niu et al., ). Meta‐analyses have revealed that the responses of plant biomass to N addition increase with mean annual precipitation (Harpole, Potts, & Suding, ; Xia & Wan, ).…”
Section: Introductionmentioning
confidence: 99%
“…In semiarid mixed conifer forests like those prevalent throughout the intermountain west, moisture frequently limits primary productivity (e.g., Hungate et al. ), but productivity in these low‐N adapted forests frequently responds positively to N additions (Shafii et al. , Brockley et al.…”
Section: Introductionmentioning
confidence: 99%